Physical and mechanical properties of thermoplastic composite from oil palm trunk / Jamaludin Kasim ...[et al.] - Kasim, Jamaludin; Mahmud, Zuhana; Ab Aziz, Abd Haqeem; Zaiton, Siti Haziah (Universiti Teknologi MARA Cawangan Pahang, 2006)
Oil palm (Elaeis Quieensis Jacq) particles were used as fillers in the manufacture of polypropylene composite. The oil palm particles were separated from the fibre strand using a vibratory screener and dried in an oven for 48 hours. Filler loading of 10%, 30% and 50% of polypropylene by weight were used in the study. Test samples were then produced using a chrome-plated mould for bending, tensile and water absorption. Results of the bending and tensile, showed that with higher filler loading, the bending and tensile strength and elongation at break decreases while modulus of elasticity increases. Water absorption decreases with increasing percentage of filler whilst MAPP addition shows no significant contribution to the composite properties. As a conclusion, particles of oil palm trunk is a suitable filler and is recommended to be used in the manufacture of thermoplastic products that does not require high strength properties.